Pengembangan Media Video Animasi Berbasis Software Powtoon Tema Transformasi Wujud Benda Untuk Menumbuhkan Minat Belajar Siswa SMP: Pengembangan Media Video Animasi Berbasis Software Powtoon Tema Transformasi Wujud Benda Untuk Menumbuhkan Minat Belajar Siswa SMP - Tasya Azizah, Ratu Annas; Suryani , Dwi Indah; Taufik, Annisa Novianti (PendIPA Journal of Science Education, 2025)
Learning interest is an important aspect that supports the success of the learning process. At the junior high school level, students tend to require engaging, interactive learning media that align with their cognitive development to foster learning interest. This study aimed to develop animated video learning media using Powtoon software on the theme Changes in the State of Matter and to analyze its level of validity as a learning medium that can enhance students’ learning interest. The media was developed by combining visual elements, animation, and simple narration to make the material more appealing and easier to understand. This study employed a Research and Development (R&D) method using the ADDIE development model, limited to the first three stages: analysis, design, and development. Validation was conducted by subject matter experts, media experts, and instructional practitioners. The validation results showed that the media achieved a validity score of 89.2%, categorized as “very valid.” These findings indicate that the developed animated video has the potential to serve as an effective alternative learning medium. However, since it has not yet been tested directly in a school environment, its implementation in the classroom still requires further trials to evaluate its effectiveness in increasing junior high school students’ learning interest.